Interventions for psychosexual dysfunction in women treated for gynaecological malignancy - Flynn, Paul (Cochrane Database Syst Rev, 2009)
BACKGROUND: Psychosexual dysfunction (sexual difficulties not directly due to physical factors) is known to be a common complication of treatment for gynaecological cancer. It has a considerable impact on quality of life (QoL) for the increasing number of women who are survivors of gynaecological cancer. OBJECTIVES: To determine the effectiveness of interventions for psychosexual dysfunction in women who have been treated for gynaecological malignancy (cancer of uterine cervix, uterine corpus, ovary, vulva). SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL, up to October 2008), MEDLINE (1950 to October 2008), EMBASE (1982 to October 2008), CINAHL (1980 to October 2008) and PsycINFO (1806 to October 2008). We hand searched reference lists from eligible trials. SELECTION CRITERIA: We selected all randomized controlled trials (RCTs) of a medical or psychological intervention to prevent or treat psychosexual dysfunction in adult women previously treated for gynaecological cancer. DATA COLLECTION AND ANALYSIS: We selected five studies for inclusion in this review and analysed any outcome data relating to resumption of sexual intercourse, DSM‐IV diagnoses or validated scales of sexual functioning. Sensitivity analysis was performed where possible. MAIN RESULTS: The review included data from 5 studies, comprising a total of 413 patients, examining 5 different interventions. One trial suggested a short‐term benefit for the use of vaginal Dienoestrol in women after pelvic radiotherapy (NNT = 4). Another trial suggested a short‐term benefit for one regime of low dose‐rate brachytherapy over another but this modality is not in widespread use. Studies of a Clinical Nurse Specialist intervention, Psychoeducational Group Therapy and a Couple‐Coping intervention, did not show any significant benefit. All the studies were of poor methodological quality. AUTHORS' CONCLUSIONS: There is no convincing evidence to support the use of any interventions for psychosexual dysfunction in women treated for gynaecological cancer. There is a need for more studies of high methodological quality.